Uso de estiercol liquido de bovino acidulado en la produccion de pimiento morron - Capulin Grande, J.=700 1 Nuñez Escobar, R.; Aguilar Acuña, J.L.; Estrada Botello, M.; Sanchez Garcia, P.; Mateo Sanchez, J.J.
(En, Es)
ilus., 28 ref.
Keywords: CAPSICUM ANNUUM; APLICACION D ABONOS; ESTIERCOL; ACIDOS ORGANICOS; ACIDOS INORGANICOS; NUTRIENTE; RENDIMIENTO; QUELACION; MEXICO